Photo-novel and photo reportage: concepts, confluences, (un)limits - Garcia, Angelo Mazzuchelli (Lumina - Revista do Programa de Pós-Graduação em Comunicação da Universidade Federal de Juiz de Fora, 2015)
Photo-novels appeared in Italy in the mid-1940’s. Several factors concurred in their creation: the personal hunch of an editor who envisioned a hybrid form between the sentimental popular romance and comics; the newspaper serials; and the illustrated film abstracts that published in the printed media. We may consider this last component the most significant: the photo-novel is, above all, a by-product of the film industry. Thus, although originally linked to the cinematographic medium, the photo-novel later became a new way of recounting original stories, enjoying great popular success in several countries like France and Brazil, besides Italy itself. Photo reportage, on the other hand, is one of the specific forms of photojournalism. Modern photojournalism originated with the German illustrated magazines of the 1920’s and 30’s. Photo reportage is not concerned with the isolated image but employs a sequence of images (photographs) to achieve a narrative logic: photo reportage must have a beginning and an ending. The present article draws a parallel between the concepts of photo-novel and photo reportage. It examines the convergences between both genres with regard to critical receptiveness both to their content and to their form – which combines text and image. It also looks at issues related with the concept of narrativity, with the aim of diluting the eventual boundaries between these two narrative forms